THE DEVELOPMENT OF TECHNOLOGY OF PROTEIN EXTRACTION AND PURIFICATION IN ZOPHOBAS MORIO - Igor Vladimirovich Rzhepakovskiy; Pavel Andreevich Trushov; Sergey Nikolaevich Povetkin; Andrei Ashotovich Nagdalian (Современная наука и инновации, 2022)
The technology of receiving a protein concentrate by discharge-pulse treatment from insects of Zophobas morio is developed. Change of coloring of the received insektoprotein which is caused by a protein fermentation by own enzymes of larvae, or enzymes of microorganisms-symbionts is established too.